Stakeholder engagement practices in social enterprises : a case study about Marula Creative Consultancy - Biasion, Gloria (2022)
Corporate social responsibility (CSR) and stakeholder engagement have gained some traction over the years, nevertheless, it still remains uncertain how much those concepts have ingrained themselves into daily business activities. Based on several scientific books and journal articles, this research will follow the development of four vital topics which are corporate social responsibility, stakeholder engagement, CSR communication and social entrepreneurship. Through a case study of a social enterprise in Uganda, this research combines management and communication research fields through an exploratory approach with the aim to understand and reveal how CSR communication processes can be a driver towards engaging stakeholders within a business setting. The case of Marula Creative Consultancy was investigated through the research methods documentation and interviews. It sought to identify the CSR activities and CSR communication activities to engage stakeholders from two different perspectives. Therefore, this master thesis explores insights from a company’s perspective and a further stakeholder perspective, namely the clients. After establishing the context of this case, the data analysis collection and analysis were conducted. The findings of this research state that stakeholder engagement is an essential part of social enterprises, and that stakeholder engagement can partially be obtained through CSR communication.